Integration of Molecular Docking in the Identification of Natural Antioxidants: Interaction Study of Jackfruit Leaf Flavonoids with NADPH:FMN Oxidoreductase - Reynaldi, Muhammad Andre; Ropiqa, Meri (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Oxidative stress plays a critical role in the progression of various degenerative diseases through increased production of reactive oxygen species (ROS), driven in spart by the activity of redox related enzymes such as NADPH:FMN oxidoreductase. Bioactive compounds from jackfruit leaves are known to possess antioxidant potential, yet their molecular mechanisms against specific enzymatic targets remain insufficiently elucidated. This study aimed to evaluate the potential interaction of jackfruit leaf flavonoids morin, oxyresveratrol, and artocarpin with NADPH:FMN oxidoreductase using molecular docking analysis. The 1BKJ protein structure was prepared following standard protocols, and all ligands were optimized prior to performing redocking for method validation. AutoDock Vina 1.2.7 was employed with a 20×20×20 Å grid box area. Redocking produced an RMSD of 0.1469 Å, confirming the reliability of the docking parameters. Docking results revealed that morin (–7.848 kcal/mol) and oxyresveratrol (–7.577 kcal/mol) exhibited stronger binding affinities compared with vitamin C (–5.713 kcal/mol) and artocarpin (–5.577 kcal/mol). The dominant interactions involved Arg15, Arg169, Tyr128, Tyr199, and Tyr200, residues that contribute to the stabilization of ligand protein complexes in silico and may be located near functionally relevant regions associated with redox activity. These findings suggest that jackfruit leaf flavonoids may serve as promising candidates for further investigation as potential modulators of redox related enzymes based on predictive in silico evidence.